Preparation method of membrane electrode microporous layer of proton exchange membrane fuel cell
By preparing the microporous layer of proton exchange membrane fuel cells by combining nanocellulose and carbon nanotubes with carbon black, the problems of insufficient conductivity and mechanical strength are solved, the pore structure is optimized, and the output performance and stability of the battery are improved.
Patent Information
- Application Number
- CN202510951257.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-10-10
AI Technical Summary
The microporous layer (MPL) of traditional proton exchange membrane fuel cells has problems such as insufficient conductivity, unreasonable pore structure, and low mechanical strength, which makes the battery prone to flooding or membrane drying at high current density, limiting the improvement of battery performance.
The membrane electrode microporous layer is prepared by using a method of synergistically compounding nanocellulose and carbon nanotubes with carbon black. By optimizing the conductivity, hydrophobicity and air permeability, the mechanical properties are enhanced, and the output power and stability of the battery are improved.
The planar and vertical resistivity of the microporous layer are significantly reduced, the pore structure is optimized, the hydrophobicity and mechanical strength are improved, the battery life is extended, and the battery's limiting current density and limiting power density under different humidity conditions are increased.
Smart Images

Figure CN120767339A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon paper, and in particular to a method for preparing a microporous layer of a membrane electrode of a proton exchange membrane fuel cell. Background Art
[0002] As a highly efficient and clean energy conversion device, the proton exchange membrane fuel cell (PEMFC) boasts significant advantages such as high energy density, fast startup, and zero emissions. It holds broad application prospects in new energy vehicles, portable power supplies, and distributed power generation. The membrane electrode assembly (MEA) is the core component of the PEMFC, while the gas diffusion layer (GDL), a key component of the MEA, performs multiple functions, including supporting the catalyst layer, conducting electrons, diffusing the reactant gases, and removing generated water. Its performance directly impacts the PEMFC's output power, stability, and durability.
[0003] The microporous layer (MPL), a key functional layer of the GDL, is typically composed of materials such as carbon black and a hydrophobic agent (such as polytetrafluoroethylene (PTFE). Its microstructure, conductivity, air permeability, hydrophobicity, and mechanical properties play a decisive role in the mass transfer efficiency and operational stability of the PEMFC. Traditional MPLs are often made from a single carbon black material, which suffers from insufficient conductivity, an illogical pore structure, and low mechanical strength. These factors can lead to PEMFCs prone to "flooding" or "membrane drying" at high current densities, limiting further improvements in cell performance.
[0004] To solve the above problems, researchers have modified MPL by introducing nanomaterials. Carbon nanotubes (CNTs) are widely used to enhance the conductive network and structural strength of MPL due to their excellent conductivity, high aspect ratio and good mechanical properties. However, CNTs are easily agglomerated in the carbon black matrix, resulting in poor dispersion and difficulty in fully exerting their performance advantages. Nanocellulose, as a green and renewable material, has a high specific surface area, rich hydroxyl functional groups and good dispersibility. It can improve the dispersibility of CNTs through interfacial effects. At the same time, the pore structure formed by the nanocellulose itself during the sintering process helps to optimize the pore distribution of MPL. Therefore, the development of an MPL preparation method based on a nanocellulose-loaded CNT / carbon black composite system has important theoretical significance and practical application value for optimizing PEMFC performance. Summary of the Invention
[0005] The present invention aims to provide a method for preparing a microporous membrane electrode layer for a proton exchange membrane fuel cell. This method utilizes nanocellulose and carbon nanotubes in combination with carbon black to create a microporous membrane electrode layer, optimizing its electrical conductivity, hydrophobicity, and air permeability, thereby enhancing the output power and stability of the proton exchange membrane fuel cell.
[0006] The technical solution of the present invention is a method for preparing a microporous layer of a membrane electrode of a proton exchange membrane fuel cell, comprising the following steps: Step 1: dispersing carbon black in anhydrous ethanol, adding carbon nanotubes to form a mixed system, and dispersing at high speed to obtain a dispersion; wherein the mass ratio of the carbon black to the carbon nanotubes is 65-95:5-35; Step 2, adding nanocellulose to the dispersion, stirring magnetically and then dispersing ultrasonically; wherein the mass ratio of the nanocellulose to the carbon black is 15-35:100; Step 3, adding polytetrafluoroethylene to the dispersion, continuing ultrasonic dispersion and stirring to form a composite slurry; wherein the mass ratio of the polytetrafluoroethylene to the carbon black is 2-4:7; Step 4: spraying the composite slurry onto carbon paper, drying, curing, and sintering to complete the preparation of the membrane electrode microporous layer of the proton exchange membrane fuel cell.
[0007] In the above-mentioned method for preparing the microporous layer of the membrane electrode of a proton exchange membrane fuel cell, in step 1, a high-speed disperser is used for dispersion at a speed of 10,000 r / min for 5 minutes.
[0008] In the aforementioned method for preparing the microporous layer of the membrane electrode of a proton exchange membrane fuel cell, in step 1, the mass ratio of the carbon black to the carbon nanotubes is 75:25.
[0009] In the aforementioned method for preparing the microporous membrane electrode layer of a proton exchange membrane fuel cell, in step 2, magnetic stirring is performed at 1000 r / min for 2 hours and then ultrasonic dispersion is performed for 30 minutes.
[0010] In the aforementioned method for preparing the microporous layer of the membrane electrode of a proton exchange membrane fuel cell, in step 2, the mass ratio of the nanocellulose to the carbon black is 20:100.
[0011] In the aforementioned method for preparing the microporous membrane electrode layer of a proton exchange membrane fuel cell, in step 3, the ultrasonic dispersion stirring is continued for 20 minutes.
[0012] In the aforementioned method for preparing the microporous layer of the membrane electrode of a proton exchange membrane fuel cell, in step 3, the mass ratio of the polytetrafluoroethylene to the carbon black is 3:7.
[0013] In the aforementioned method for preparing the microporous layer of the membrane electrode of the proton exchange membrane fuel cell, in step 4, the curing temperature is 250°C and the curing time is 30 minutes; the sintering heating rate is 5°C / min, the sintering temperature is 350°C, and the sintering time is 30 minutes.
[0014] In the aforementioned method for preparing the microporous layer of the membrane electrode of a proton exchange membrane fuel cell, in step 2, the nanocellulose is selected from any one of the following: cellulose nanocrystals with a length of 40 nm; cellulose nanofibers with a length of 5 μm; Cellulose nanofibers with a length of 20 μm.
[0015] Compared with the existing technology, the present invention prepares the membrane electrode microporous layer (MPL) of the proton exchange membrane fuel cell by synergistically compounding nanocellulose and carbon nanotubes (CNT) with carbon black, which has the following beneficial effects: First, nanocellulose is used to improve the dispersibility of CNT, enhance the interfacial bonding between the two, avoid CNT agglomeration, give full play to its conductive advantages, significantly reduce the plane resistivity and vertical resistivity of MPL, and optimize the conductive performance; second, by regulating the amount of CNT added and the length of nanocellulose, the pore structure of MPL is optimized, the air permeability and porosity are improved, and the surface hydrophobicity is improved, effectively solving the "flooding" problem in the operation of the fuel cell and promoting gas diffusion and mass transfer efficiency; third, the mechanical properties of MPL are enhanced, the tensile strength and stress-strain values are increased, and the thermal stability and electrochemical carbon corrosion resistance are improved, extending the service life of the gas diffusion layer (GDL) and the battery; fourth, the assembled proton exchange membrane fuel cell exhibits higher limiting current density and limiting power density under different humidity conditions, significantly improving the output performance and operational stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The microstructures of MPL prepared by CNT / nanocellulose composite VXC carbon black with different lengths. (a) CNT-5 / CNF1-20 (front view); (b) CNT-15 / CNF1-20 (front view); (c) CNT-25 / CNF1-20 (front view); (d) CNT-35 / CNF1-20 (front view); (e) CNT-5 / CNF1-20 (cross-section); (f) CNT-25 / CNF1-20 (cross-section); (g) CNT-25 / CNC-20 (cross-section); and (h) CNT-25 / CNF2-20 (cross-section). Figure 2 The physical properties of GDL prepared by nanocellulose / CNT composite VXC carbon black with different lengths. (a) XRD pattern; (b) plane resistivity; (c) MPL roughness value; (d) surface water contact angle; (e) vertical resistivity and (f) volume density; Figure 3 The pore structure characteristics of GDL prepared by nanocellulose / CNT composite VXC carbon black with different lengths. (a) GDL permeability at 400 Pa; (b) GDL permeability at different pressures; (c) porosity and (d) pore size distribution; Figure 4Electrochemical performance of MPL-impregnated GDL prepared with nanocellulose / CNT composite VXC carbon black of different lengths. (a) TG; (b) DTG; (c) Tafel plot and (d) electrochemical impedance spectroscopy (EIS); Figure 5 Mechanical strength analysis of GDL prepared from nanocellulose / CNT composites with VXC carbon black of different lengths. (a) Tensile strength; (b) Stress-strain curves and (c) Laser scanning confocal microscopy images. Figure 6 Figure 2. Performance of PEMFCs assembled with GDLs fabricated from nanocellulose / CNT composites with VXC carbon black and different lengths under low, medium, and high humidity conditions. (a) Polarization curve and power density at RH = 40%; (b) EIS impedance curve at RH = 40%; (c) Polarization curve and power density at RH = 70%; (d) EIS impedance curve at RH = 70%; (e) Polarization curve and power density at RH = 100%; and (f) EIS impedance curve at RH = 100%. DETAILED DESCRIPTION
[0017] The present invention will be further described below with reference to the accompanying drawings and examples, but they are not intended to limit the present invention.
[0018] Example: A method for preparing a microporous layer of a membrane electrode for a proton exchange membrane fuel cell. The experimental raw materials and reagents are shown in Table 1:
[0019] Table 1 The experimental instruments and equipment are shown in Table 2:
[0020] Table 2 The steps include: Step 1. Weigh 2.8g of VXC carbon black in anhydrous ethanol in a conical flask, then add different amounts of carbon nanotubes (CNTs) to form a mixture in which the total mass of carbon black and CNTs in the entire dispersion system (anhydrous ethanol solvent) is 5.6wt%. Then, use a high-speed disperser to disperse the mixture at a speed of 10,000 r / min for 5 minutes to ensure that the components are fully and evenly mixed. In this step, the addition amount standard is as follows: the mass ratio of carbon black to carbon nanotubes is 65-95:5-35. The carbon nanotubes are named according to their mass ratio. There are four different addition amounts of carbon nanotubes: CNT 5wt%, CNT 15wt%, CNT 25wt%, and CNT 35wt%, thereby forming four mixtures with different mass ratios. Step 2: Pour dispersions of different nanocellulose forms (cellulose nanocrystals (CNCs) with a length of 40 nm; cellulose nanofibers (CNF1) with a length of 5 μm; and cellulose nanofibers (CNF2) with a length of 20 μm) into a conical flask. The mass ratio of nanocellulose to carbon black was 20:100, meaning the mass specific gravity of the nanocellulose was 20 wt%. With the aid of a magnetic stirrer, the mixture was stirred continuously at 1000 rpm for 2 hours and ultrasonically dispersed for 30 minutes. In this step, the following six composition combinations were formed: CNT 5 wt% + CNF1 20 wt%, CNT 15 wt% + CNF1 20 wt%, CNT 25 wt% + CNF1 20 wt%, CNT 35 wt% + CNF1 20 wt%, CNT 25 wt% + CNC 20 wt%, and CNT 25 wt% + CNF2 20 wt%. Step 3: Add polytetrafluoroethylene (PTFE) to the mixed system at a mass ratio of PTFE to VXC carbon black of 3:7, and continue ultrasonic dispersion and stirring for 20 minutes to form a uniform nanocellulose / CNT synergistic composite VXC carbon black slurry. In this step, the MPLs prepared from nanocellulose / CNT synergistic composite VXC carbon black with different fiber lengths are named CNT-m / CNC-n and CNT-m / CNF-n, where m represents the CNT composite content and n represents the CNC or CNF composite content (Table 3):
[0021] Table 3 Step 4: Cut the Toray carbon paper into 5 cm × 5 cm size, and use a spray gun to evenly spray different nanocellulose / CNT composite VXC carbon black slurries on the carbon paper surface. Use an electronic balance to weigh the sample to ensure that the carbon loading reaches 1.25 mg cm -2 After natural drying at room temperature for 3 h, the sample was placed in a muffle furnace and cured at 250°C for 30 min. After that, the temperature was raised to 350°C at a heating rate of 5°C / min and sintered for 30 min to form pores in the nanocellulose. After cooling, a GDL with nanocellulose / CNT composite VXC carbon black-based MPL was obtained.
[0022] The microscopic morphology of the MPL prepared by nanocellulose loaded with CNT / VXC carbon black in this example was analyzed. Figure 1Microstructures of MPL prepared from CNT / nanocellulose composite VXC carbon black with different lengths. (a) CNT-5 / CNF1-20 (front view); (b) CNT-15 / CNF1-20 (front view); (c) CNT-25 / CNF1-20 (front view); (d) CNT-35 / CNF1-20 (front view); (e) CNT-5 / CNF1-20 (cross-section); (f) CNT-25 / CNF1-20 (cross-section); (g) CNT-25 / CNC-20 (cross-section) and (h) CNT-25 / CNF2-20 (cross-section). Figure 1 As can be seen from the ad graph, as the amount of CNT added increases from 5 wt% to 25 wt%, the CNF fibrils on the MPL surface gradually decrease, and the surface particle stacking gradually becomes denser. When the CNT addition reaches 35 wt%, the MPL surface becomes dense and flat, and the pore structure is obvious. The reason for this phenomenon is that when CNT and CNF1-20 are synergistically compounded, CNF1-20 and CNT first fill the pores between the carbon black particles, and then CNF1-20 forms a pore structure on the MPL surface during the sintering process. When 25 wt% of CNT is added and mixed with carbon black particles, the pore filling is most reasonable. From the cross-sectional diagram of CNT-25 / CNF1-20 GDL ( Figure 1 (f) Comparison shows that MPL is more tightly bonded to the carbon paper layer and has better surface smoothness. When the CNT addition amount is 25 wt%, Figure 1 The cross-sectional MPL layer of CNT-5 / CNF1-20 in Figure e and CNT-25 / CNF2-20 in Figure f is tightly bound to the carbon paper interface. Figure 1 CNT-25 / CNC-20 in Figure g and CNT-25 / CNF2-20 in Figure h showed obvious cracks and had a loose structure. This is because fibers that are too long or too short are difficult to disperse during the composite preparation with CNTs, resulting in excessively high cellulose concentration in local areas. During the sintering process, cracks appear due to uneven shrinkage of nanocellulose.
[0023] The XRD, resistivity, roughness, water contact angle and bulk density of MPL and GDL prepared by synergistically combining nanocellulose and CNT with VXC carbon black of different lengths were analyzed. Figure 2 shown. Figure 2 The physical properties of GDLs prepared with nanocellulose / CNT composites and VXC carbon black of varying lengths are shown: (a) XRD patterns; (b) in-plane resistivity; (c) MPL roughness; (d) surface water contact angle; (e) perpendicular resistivity; and (f) bulk density.
[0024] Depend on Figure 2It can be seen from a that there are only these two peaks in the sample, which are mainly the (002) crystal structure of graphite, and the sample has a high degree of crystallinity. This shows that the overall structure of the MPL prepared by compounding each nanocellulose with CNT can maintain uniformity and integrity. The synergy between CNT and nanocellulose improves the degree of graphitization of the material and can effectively improve its conductivity. Figure 2 As shown in Figure b, as the CNT loading increases from 5 wt% to 35 wt%, the MPL in-plane resistance first decreases from 42.5 mΩ·cm to 36.4 mΩ·cm and then increases to 47.6 mΩ·cm. This indicates that the MPL in-plane resistivity exhibits a pattern of first decreasing and then increasing with increasing CNT loading in the VXC carbon black. At a CNT loading of 25 wt%, as the nanocellulose fiber length increases, the MPL in-plane resistance first decreases from 49.8 mΩ·cm to 36.4 mΩ·cm and then increases to 47.9 mΩ·cm, similarly exhibiting a pattern of first decreasing and then increasing. CNT-25 is deposited at different angles within the carbon black particles, filling the existing pores in the MPL coating and reducing the surface resistivity. At the same CNT-25 loading, as the nanocellulose fiber length increases, the agglomerated fibers and CNTs become less dispersed, resulting in an increase in resistivity.
[0025] like Figure 2 As shown in c and d, the surface roughness has a significant effect on the results of the water contact angle. The MPL surface is not ideally smooth, and the roughness will significantly change the contact behavior between the droplet and the surface. As the CNT addition amount increases from 5wt% to 35wt%, the surface roughness first decreases from 2.23μm to 1.68μm and then increases to 1.98μm. As the surface roughness increases, the water droplet will experience contact angle hysteresis on the rough surface, resulting in a significant change in the MPL water contact angle. When the CNT addition amount is the same, as the length of the nanocellulose fibers increases, the surface contact angle of MPL increases from 136° to 143° and then decreases to 139°. The lower surface roughness reduces surface defects and irregular structures, thereby improving the hydrophobic properties of MPL.
[0026] from Figure 2As can be seen, the vertical resistivity of GDLs prepared from nanocellulose of varying lengths and CNTs combined with VXC carbon black all exhibits a trend of first decreasing and then stabilizing. Under a test pressure of 0.1 MPa, as the CNT addition increases from 5wt% to 35wt%, the vertical resistivity of the GDL first decreases from 95.5mΩ·cm to 39.8mΩ·cm and then increases to 57.32mΩ·cm, consistent with the planar resistivity pattern. This phenomenon is attributed to the formation of a conductive network within the GDL by the addition of CNTs, effectively reducing the vertical resistivity. However, when the CNT addition exceeds 25wt%, the CNTs aggregate and become unevenly distributed. The small pores created by the nanocellulose inhibit the overall conductivity, thereby increasing the GDL resistivity. Similarly, when the CNT addition amount is 25wt%, as the length of nanocellulose fibers increases, the vertical resistance of GDL first decreases from 73.6mΩ·cm to 39.8mΩ·cm and then increases to 66.9mΩ·cm. As the length of nanocellulose fibers increases, their ability to disperse CNTs is enhanced, and CNTs are evenly distributed in MPL, thereby reducing its vertical resistivity. However, excessively long CNF fiber length may cause uneven distribution of CNTs, destroy the integrity of the conductive network, and cause the vertical resistivity of GDL to rise again.
[0027] from Figure 2 It can be seen from f that as the CNT addition amount increases from 5wt% to 25wt%, the bulk density gradually increases, and the bulk density of CNT-35 / CNF1-20 GDL is the highest (0.68g·cm -3 ), the internal structure is the most compact and the porosity is low, which is mainly due to the fact that the pores in the internal structure of MPL can be filled after the CNT and nanocellulose are mixed. When the CNT addition amount is 25wt%, as the nanocellulose fiber length increases, the bulk density of GDL (CNT-25 / CNC-20, CNT-25 / CNF1-20, CNT-25 / CNF2-20) is 0.66g·cm -3 , 0.61 g·cm -3 , 0.61 g·cm -3 , showing a pattern of first decreasing and then stabilizing. This is because the longer fibers become looser after mixing with the CNTs, forming larger pores. However, excessively high bulk density may increase the water vapor transmission resistance during fuel cell operation, resulting in uneven water vapor transmission and reduced battery output efficiency.
[0028] The pore structure characteristics of GDL prepared by nanocellulose loaded with CNT / VXC carbon black were analyzed. Figure 3 shown. Figure 3Pore structure characteristics of GDL prepared from nanocellulose / CNT composites with VXC carbon black of different lengths. (a) GDL air permeability at 400 Pa; (b) GDL air permeability at different pressures; (c) porosity and (d) pore size distribution.
[0029] Depend on Figure 3 As shown in a, under a pressure of 400 Pa, at the same nanocellulose addition of 20 wt%, as the CNT addition increased from 5 wt% to 35 wt%, the GDL permeability first increased from 225 L·m -2 ·s -1 Increased to 375 L·m -2 ·s -1 , and then reduced to 300 L·m -2 ·s -1 , showing a regular trend of first increasing and then decreasing. Figure 3 Figure b shows the air permeability of GDL at different pressures. As the test pressure gradually increased, the air permeability of all GDL samples showed a continuous upward trend. This phenomenon is due to the fact that after sintering, CNTs and nanocellulose can penetrate and fill the pores within the carbon black particles, resulting in a high pore volume. This enhances gas transmission and increases air permeability.
[0030] like Figure 3 As shown in Figure c, under the same nanocellulose addition conditions, as the CNT addition increases from 5 wt% to 35 wt%, the GDL porosity rises from 72.96% to 77.54% and then decreases to 74.87%, showing a pattern of initial increase followed by decrease. This is because the addition of a small amount of CNTs promotes dispersion among carbon blacks, increasing porosity. However, when excessive CNTs are added, the pores in the carbon black become clogged, resulting in a decrease in overall porosity. Under high load conditions, water flooding easily occurs, affecting battery performance.
[0031] Depend on Figure 3As shown in Figure d, as the CNT addition increases from 5 wt% to 25 wt%, the pore size distribution of the GDL gradually widens. The number of micropores (0-10 μm) increases, the number of small pores (10-20 μm) remains essentially unchanged, the number of mesopores (20-30 μm) decreases, and the number of macropores (30-60 μm) also increases. When the CNT addition reaches 35 wt%, the pore size of the GDL's micropores (0-10 μm) decreases, the number of small pores (10-20 μm) remains essentially unchanged, the number of mesopores (20-30 μm) decreases, and the number of macropores (30-60 μm) also decreases. This phenomenon is attributed to the high aspect ratio of CNTs, which can increase the complex network structure within the MPL, increasing the diversity of pores and leading to a wider pore size distribution. According to the results of porosity and pore size distribution, CNT-25 / CNF1-20 was selected as the optimal addition amount in carbon black. The loose stacking between CNT and nanocellulose helps to adjust and optimize the pore size distribution of MPL. Reasonable pore size distribution will improve the transmission efficiency of gas and water.
[0032] The thermogravimetric and Tafel stability of MPL prepared by nanocellulose loaded with CNT / VXC carbon black were analyzed. The thermogravimetric and Tafel curves of MPL prepared by synergistic composite of nanocellulose and CNT with VXC carbon black of different lengths were shown in Figure 2. Figure 4 Shown are (a) TG; (b) DTG; (c) Tafel plot and (d) electrochemical impedance spectroscopy (EIS).
[0033] Depend on Figure 4 It can be seen from a that the final residual mass of CNT-5 / CNF1-20 MPL reaches 92.25%. When the CNT addition amount is 5 wt%, the nanocellulose decomposes less and is less affected by the high-temperature thermal decomposition reaction, indicating that the pore structure formed in the MPL is less. When the CNT addition amount increases from 5 wt% to 35 wt%, the final residual mass of MPL increases from 86.92% to 83.33%. A larger amount of CNT addition or a very small amount of CNT addition can promote the decomposition of nanocellulose at high temperature and can produce more pores inside the MPL. At the same time, all MPL samples did not have a large mass loss before 500oC, and the maximum weight loss rate occurred at 563oC ( Figure 4 b), indicating that MPL has good thermal stability and meets the normal operating conditions of PEMFC.
[0034] Depend on Figure 4 As shown in c, as the CNT addition amount increases from 5 wt% to 35 wt%, the GDL corrosion current density increases from 136 μA·cm -2 Reduced to 0.176 μA·cm -2 Then it increased to 0.59 μA·cm -2, the GDL corrosion potential decreased from 0.58 V to 0.39 V and then increased to 0.89 V, both showing a trend of first decreasing and then increasing, indicating that the GDL electrochemical carbon corrosion resistance first gradually increased and then weakened. The reason for this phenomenon is that the addition of CNT can form an effective carbon skeleton network structure in the MPL, enabling the GDL to better resist the corrosion of the corrosion solution, thereby improving the durability of the PEMFC. Combined with Figure 4 d, the impedance values of CNT-25 / CNF1-20 and CNT-35 / CNF1-20 were 862 kΩ and 891 kΩ, respectively, and the values were relatively close, indicating that CNT-25 / CNF1-20 and CNT-35 / CNF1-20 had good electrochemical carbon corrosion resistance. It can be inferred that the GDL electrochemical carbon corrosion resistance is related to the amount of CNT added. The ring-like graphite structure of CNT is not easily corroded by corrosive media. The strength properties and microstructure of GDL prepared by nanocellulose supported CNT / VXC carbon black were analyzed. The strength properties, stress-strain, and laser scanning confocal microscopy of GDL prepared by nanocellulose and CNT of different lengths and VXC carbon black were characterized, as shown in Figure 5 (a) tensile strength; (b) stress-strain curve; and (c) laser scanning confocal microscopy.
[0035] As shown in Figure 5 a, with the increase of CNT addition amount from 5 wt% to 35 wt%, the tensile strength of GDL showed a trend of first increasing and then decreasing, from 14.5 MPa to 17.2 MPa, and then decreasing to 15.8 MPa, indicating that under the same amount of nanocellulose, the optimal amount of CNT addition was 25 wt%. In addition, with the same amount of CNT addition, the tensile strength also increased from 15.7 MPa to 17.2 MPa and then decreased to 14.9 MPa with the increase of nanocellulose fiber length.
[0036] Figure 5 b, with the increase of CNT addition amount from 5 wt% to 35 wt%, the maximum value of GDL stress-strain first increased from 18.44 MPa to 36.42 MPa and then decreased to 28.94 MPa, showing a trend of first increasing and then decreasing. The MPL prepared by CNT-25 / CNF1-20 group composite had the strongest stress-strain value, reaching 36.42 MPa. The reason is that the high aspect ratio of CNT can enhance the connection strength between carbon black, thereby enhancing the strength properties of GDL.
[0037] As shown in Figure 5As shown in Figure c, the surfaces of CNT-5 / CNF1-20 MPL and CNT-15 / CNF1-20 MPL showed a large area of red and blue, indicating that the roughness of the MPL surface was large, and the small amount of CNT added had little effect on the surface of the MPL. When the CNT addition amount increased from 5 wt% to 25 wt%, the MPL surface morphology showed a more uniform color, and the roughness gradually decreased. Under the condition of 25 wt% CNT addition, with the increase of the length of the nanocellulose fibers, the roughness showed a trend of first decreasing and then increasing. This may be because the CNT and nanocellulose can be better dispersed with the carbon black particles after mixing, thereby reducing the surface roughness, which is consistent with the Figure 2 cThe results are consistent.
[0038] The electrochemical performance of PEMFC was analyzed. The polarization curves, power density and electrochemical impedance spectroscopy (EIS) of PEMFC assembled with GDL prepared by nanocellulose with different lengths and VXC carbon black under different working conditions are shown in the figure. Figure 6 As shown, (a) RH=40% polarization curve and power density; (b) RH=40% EIS impedance curve; (c) RH=70% polarization curve and power density; (d) RH=70% EIS impedance curve; (e) RH=100% polarization curve and power density and (f) RH=100% EIS impedance curve.
[0039] When the PEMFC operating humidity is 40% RH ( Figure 6 a) As the CNT content increases from 5 wt% to 35 wt%, the PEMFC limiting current density increases from 1.15 A·cm -2 Increased to 1.39 A·cm -2 Then it was reduced to 1.35 A·cm -2 , the ultimate power density is from 0.43 W·cm -2 Increased to 0.48 W·cm -2 Then it was reduced to 0.45 W·cm -2 , increased by 20.87% and 11.63% respectively; it can be seen that with the increase of CNT addition, the limiting current density and limiting power density of GDL assembled PEMFC show a change pattern of first increasing and then decreasing. In addition, the EIS impedance diagram ( Figure 6b) As can be seen, when the PEMFC operating humidity is 40% RH, the curvature of the PEMFC EIS curve gradually decreases and then increases as the CNT addition increases from 5 wt% to 35 wt%. When the CNT-25 content remains constant, the curvature of the PEMFC curve initially decreases and then increases as the nanocellulose fiber length increases. This phenomenon is attributed to the optimal permeability and porosity of the GDL prepared with CNT-25 / CNF1-20. Liquid water and gas converge and are rapidly discharged, resulting in minimal mass transfer polarization, effectively preventing flooding and achieving the highest ultimate power density, thus demonstrating excellent battery performance.
[0040] from Figure 6 c It can be seen that when the PEMFC operating humidity is 70% RH, as the CNT addition amount increases from 5 wt% to 35 wt%, the PEMFC current density increases from 1.24 A·cm -2 Increased to 1.45 A·cm -2 Then it was reduced to 1.38 A·cm -2 , the ultimate power density is from 0.36 W·cm -2 Increased to 0.49 W·cm -2 Then it dropped to 0.41 W·cm -2 , which increased by 16.94% and 36.11% respectively; and when the PEMFC operating humidity was 100% RH, as the CNT addition amount increased from 5 wt% to 35 wt%, the PEMFC limiting current density increased from 1.14 A·cm- 2 Increased to 1.30 A·cm -2 Then it was reduced to 1.28 A·cm -2 , the ultimate power density is from 0.33W·cm -2 Increased to 0.47 W·cm -2 Then it was reduced to 0.39 W·cm -2 , an increase of 14.03% and 42.42% respectively.
[0041] It can be seen that under the operating humidity conditions of 40% RH, 70% RH and 100% RH, the limiting current density and limiting power density of PEMFC both show a change pattern of first increasing and then decreasing. The reason for this phenomenon is that the pores of CNT-25 and nanocellulose in the preparation of MPL are well integrated with the carbon paper interface. Reasonable pores can quickly achieve drainage and exhaust, and can maintain good transmission performance. Figure 6 As shown in d and f, when the PEMFC operating humidity is 70% RH and 100% RH, the curvature of the EIS curve shifts slightly to the left with the increase in the amount of CNT added, indicating that the ohmic impedance of the PEMFC decreases during operation, which is consistent with the polarization curve results. The battery performance is significantly optimized and exhibits excellent performance.
[0042] In summary, the application optimizes the conductivity, hydrophobicity, air permeability and other properties of the membrane electrode microporous layer prepared by the synergistic composite of nanocellulose and carbon nanotubes, and improves the output power and stability of the proton exchange membrane fuel cell.
Claims
1. A method for preparing a microporous layer of a membrane electrode for a proton exchange membrane fuel cell, characterized in that: The steps include: Step 1, dispersing carbon black in anhydrous ethanol, adding carbon nanotubes to form a mixed system, and dispersing at high speed to obtain a dispersion; wherein the mass ratio of the carbon black to the carbon nanotubes is 65-95:5-35; Step 2, adding nanocellulose to the dispersion, stirring magnetically and then dispersing ultrasonically; wherein the mass ratio of the nanocellulose to the carbon black is 15-35:100; Step 3, adding polytetrafluoroethylene to the dispersion, continuing ultrasonic dispersion and stirring to form a composite slurry; wherein the mass ratio of the polytetrafluoroethylene to the carbon black is 2-4:7; Step 4: spraying the composite slurry onto carbon paper, drying, curing, and sintering to complete the preparation of the membrane electrode microporous layer of the proton exchange membrane fuel cell.
2. The method for preparing a proton exchange membrane fuel cell membrane electrode microporous layer according to claim 1, characterized in that: In step 1, a high-speed disperser is used for dispersion at a speed of 10,000 r / min for 5 minutes.
3. The method for preparing a proton exchange membrane fuel cell membrane electrode microporous layer according to claim 1, characterized in that: In step 1, the mass ratio of the carbon black to the carbon nanotubes is 75:
25.
4. The method for preparing a proton exchange membrane fuel cell membrane electrode microporous layer according to claim 1, characterized in that: In step 2, magnetic stirring was performed at 1000 r / min for 2 h and then ultrasonic dispersion was performed for 30 min.
5. The method for preparing a proton exchange membrane fuel cell membrane electrode microporous layer according to claim 1, characterized in that: In step 2, the mass ratio of the nanocellulose to the carbon black is 20:
100.
6. The method for preparing a proton exchange membrane fuel cell membrane electrode microporous layer according to claim 1, characterized in that: In step 3, the ultrasonic dispersion stirring time is continued for 20 minutes.
7. The method for preparing a proton exchange membrane fuel cell membrane electrode microporous layer according to claim 1, characterized in that: In step 3, the mass ratio of the polytetrafluoroethylene to the carbon black is 3:
7.
8. The method for preparing a proton exchange membrane fuel cell membrane electrode microporous layer according to claim 1, characterized in that: In step 4, the curing temperature is 250° C. and the curing time is 30 min; the sintering heating rate is 5° C. / min, the sintering temperature is 350° C., and the sintering time is 30 min.
9. The method for preparing a proton exchange membrane fuel cell membrane electrode microporous layer according to claim 1, characterized in that: In step 2, the nanocellulose is selected from any one of the following: cellulose nanocrystals with a length of 40 nm; cellulose nanofibers with a length of 5 μm; Cellulose nanofibers with a length of 20 μm.